CEO Over-confidence and Corporate Cash Holdings: Emphasizing the Moderating Role of Audit Quality - Narges Sarlak; Omid Faraji; Mostafa Ezadpour; Zahra Joudaki Chegeni (بررسی‌های حسابداری و حسابرسی, 2018)
Objective: Since cash has a pivotal role in going concern, financial flexibility and utilizing investment opportunities, managers have sufficient motivation to hold cash. The existence of an overconfidence attribute in managers leads to an over-estimation of their knowledge and their ability to generate future cash flows. This process can affect their decision on investing in projects and amount of cash holdings; on the other hand, audit quality is an effective mechanism for controlling managerial decisions and issues related to investment plans. Hence, the main purpose of this study is to investigate the effect of audit quality on the relationship of CEO overconfidence and cash holdings. Methods: Hypotheses have been investigated using a sample of 170 companies listed in the Tehran Stock Exchange during the period 2012-2016 and multiple regression equations of integrated data method. Findings: The authors find that there is a negative relationship between managers' overconfidence and cash holdings. Further, audit quality audits do not reduce the intensity of the negative relationship between managers' overconfidence and cash holdings. Conclusion: Based on the results, overconfidence managers are less willing to cash holding, because of their excessive self-reliance and ignoring demand for cash. In addition, contrary to theoretical foundations of research, audit quality does not affect the relationship between overconfidence and cash holdings. This can be due to Inappropriate of audit quality measurement metrics in Iran and ineffectiveness of audit quality in preventing of behavior managers overconfidence.